A Deteriorating Inventory Model with Ramp Type Demand and Time Dependent Holding Cost - Vinita Singh, Kapil Dave, Sanjay Singh, Garima Garg (Mathematical Statistician and Engineering Applications, 2022)
In this paper, an inventory model has been developed with ramp type demand and time-dependent holding cost. At the beginning of the cycle, the holding cost increases linearly with time and then becomes constant. The effect of deterioration has been taken into account and considered as a linearly increasing function of time. The main objective of the proposed paper is to derive the inventory policies for minimizing the total cost involved in developing inventory model. The convexity of the total cost has been shown graphically. Also, a numerical example has been solved to illustrate and validate the model.